PENGARUH SENSORY BRANDING TERHADAP PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN INDOMIE DI KABUPATEN PEKALONGAN - Prahadi Khairul Musa, Zainul; Satrio, Danang (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
Companies in this era must be able to carry out appropriate marketing strategies to attract consumer interest and attention. Apart from grouping consumers in terms of demographics, marketers must start trying psychological approaches in marketing, one of which is sensory branding. The purpose of this research is to determine the influence of sensory branding (Sight, Sound, Smell, Touch and Taste) on consumer behavior in making purchasing decisions for Indomie in Pekalongan Regency. This quantitative research uses multiple linear regression analysis techniques. The population of this research is Indomie consumers in Pekalongan Regency. Sampling in this study used a purposive sampling technique and sample calculation was carried out using the Slovin formula until a sample of 100 people was determined. The results of the analysis show that partially Sensory Branding (Sight, Sound, Touch, Taste) has a significant positive influence on consumer behavior in making decisions to purchase Indomie in Pekalongan Regency, and Smell has no effect on consumer behavior in making decisions to purchase Indomie in Pekalongan Regency, whereas Simultaneously, noted that there is a significant influence between Sensory Branding (Sight, Sound, Smell, Touch and Taste) on consumer behavior in making Indomie purchasing decisions in Pekalongan Regency.